The effectiveness of mobile—AI applications in enhancing English reading skills: an experimental study among Jordanian primary school students - Al-Nawaiseh, Sabah Jamil (Frontiers in Education, 2026)
The study investigates the effect of using mobile-based Artificial Intelligence (AI) applications on the development of English reading skills among primary students in Jordan. The researcher employed a quasi-experimental design. The sample consisted of 60 fifth-grade students selected using purposive sampling and assigned to two group: an experimental group of 30 students who received instruction through a mobile AI- application and a control group of 30 students who were taught using traditional methods. Traditional instruction relied on teacher explanation, textbook-based activities, and conventional drills, with students required to read aloud to the teacher, who monitored their progress. Students were also required to read the text aloud to the teacher, who monitored their progress during reading. The study was conducted at Independent International Schools during the 2024–2025 academic year. The study instrument consisted of an observation checklist. The results indicated statistically significant differences between the two groups, favoring the experimental group (F(1,57) = 149.619, p < 0.001, η2 = 0.710), which was attributed to the use of AI applications in teaching reading skills. The study recommended organizing training workshops for teachers to familiarize them with AI applications that support and enhance teaching, as well as adopting new strategies aligned with modern technological advancements to meet students’ needs and interests. These findings suggest that AI applications can enhance reading skills and highlight the importance of teacher training and further research on AI-assisted learning.